Umeclidinium for the treatment of uncontrolled asthma. (3rd June 2017) - Ferrando, Matteo; Bagnasco, Diego; Braido, Fulvio; Baiardini, Ilaria; Passalacqua, Giovanni; Puggioni, Francesca; Varricchi, Gilda; Canonica, Giorgio Walter
ABSTRACT: Introduction : Smooth muscle cell contraction in the airways is the principal therapeutic target in asthmatic subjects and its insufficient treatment is often a cause of uncontrolled disease. For this reason, research has focused on targeting smooth muscle activity with anticholinergic agents, including umeclidinium. Areas covered : This review highlights the potential application of umeclidinium, a long acting muscarinic antagonist, as a novel therapeutic approach for patients with severe uncontrolled asthma, despite maximal therapy. Expert opinion : Umeclidinium, similarly to tiotropium, which has been recently included in guidelines, may act by contrasting cholinergic activation in airways, preventing or at least reducing smooth muscle cells contraction and the consequent bronchoconstriction. This is similar to what occurs in chronic obstructive pulmonary disease, for which umeclidinium has been regularly approved. However, available data is not sufficient and further studies are needed before regulatory approval can be sought, since only phase II clinical trials have been conducted at present. Both quality of life and objectifiable clinical data and parameters must be assessed, including lung function improvements, reduction of exacerbations and reduction of as required medications.